"Not by Might, Nor by Power": Spirit-filled Imaginary for Peace Building in Romania. (October 2022) - Mocan, Beneamin
Peace building in our societies should be central to Christian theology. In a postcommunist culture as is the case of Romania, part of the task of Christian theology is to construct the proper trajectories to peace building by looking back at the time when the Church was trapped in dictatorial clutches. Referring to the Pentecostal Church in Romania, we will see that the best way of bringing to light the possible contributions towards peace building is by making use of the category of "imaginary". This category helps us both to uncover the decisive identity markers of a given spirituality and to find those much-needed contributions towards peace building.